Are we doing enough to prevent a heart disease epidemic? - Mpe, Martin T. (SA Heart Journal, 2017)
This editorial is intended to provoke debate on the relevance of our contribution and its impact on the health care challenges faced by our entire population amidst the current financial and human resource constraints.